ANALISIS FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK UMUM SWASTA NASIONAL DEVISA - Hikmah Hikmah (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
This research was conducted with the aim to find out in part the Influence of Loan Deposit Ratio (LDR), Non Performing Loan (NPL), and Net Interest Margin (NIM) partially on profitability (ROA) on Private Foreign Exchange Banks listed on the Indonesia Stock Exchange. This research uses quantitative research methods with descriptive types of research. The population in the study was 28 private banks with a sample of 7 foreign exchange banks with a five-year research period ranging from 2017  - 2020. The sample selection technique uses the purposive sampling method. The results of the t test showed that LDR and NIM had a significant effect on ROA. The NPL has no significant effect on ROA. The F test results concluded that LDR, NPL, and NIM simultaneously had a significant effect on ROA